Quality of experience–oriented fuzzy routing decision by combining multiple attributes experience data - Lingmin Yang; Hong Wang; Shunying Zhu; Changhua Yao; Junye Meng (International Journal of Distributed Sensor Networks)
The routing decisions of information data are important to many intelligent systems, such as transporting system. The quality of experience in the routing decisions has drawn attention in recent works. This article studies the quality of experience–oriented routing decision problem using the vacillating fuzzy analysis approach. The integration operators and multiple attribute routing decision method based on multiple unsure information are studied. The experimental results show that the proposed approach solves the personal experience–oriented routing decision problem by improving the qualification of experience under the unsure and uncompleted information conditions.